Locally derived traffic-related air pollution and fetal growth restriction: A retrospective cohort study - Pereira, Gavin; Cook, A.; Haggar, F.; Bower, C.; Nassar, N. (2012)
Background: Fetal growth restriction has been inconsistently associated with maternal exposure to elevated levels of traffic-related air pollution. Objective: We investigated the relationship between an individualised measure of fetal growth and maternal exposure to a specific marker for traffic-related air pollution. Methods: We estimated maternal residential exposure to a marker for traffic-related air pollution (nitrogen dioxide, NO2) during pregnancy for 23 452 births using temporally adjusted land-use regression. Logistic regression was used to investigate associations with small for gestational age and sex (SGA) and fetal growth restriction, defined as proportion of optimal birth weight (POBW) below the 10th percentile. Sub-populations investigated were: women who spent most time at home, women who did not move house, women with respiratory or circulatory morbidity, women living in low/middle/high socio-economic areas, women who delivered before 37 weeks gestation, and women who delivered from 37 weeks gestation. Results: An IQR increase in traffic-related air pollution in the second trimester across all women was associated with an OR of 1.31 (95% CI 1.07 to 1.60) for fetal growth restriction. Effects on fetal growth restriction (low POBW) were highest among women who subsequently delivered before 37 weeks of gestation. Effects on SGA were highest among women who did not move house: OR 1.35 (95% CI 1.08 to 1.69). Conclusions: Larger effect sizes were observed for low POBW than for SGA. Exposure to traffic-related air pollution in mid to late pregnancy was associated with risk of SGA and low POBW in this study.